Students’ Cognitive, Attitudinal, and Behavioral Factors in Mosquito Larvae Surveillance for Aedes Habitat Elimination to Prevent Dengue Transmission - Siti Rahmatia Bau; Andi Helmy Ishak (Inspire Global Insight Journal, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus through a dengue vector whose case rate is currently quite high in Indonesia. This study uses a survey method and a quasi-experimental approach (Quasi Experimental) with a Nonrandomized Control Group Pretest-Posttest Design. This study involved two different groups. The Intervention Group was grade VIII students of SMPN 49 Makassar City and SMPN 21 Makassar City as the control group. The number of samples was 60 respondents with a sampling selection method, namely Purposive Sampling. The instruments used were research questionnaires, DHF booklets, PSN-Kit, larva monitoring checklists, observation sheets and so on. Results: There were differences in the values of knowledge, attitudes and actions of respondents before and after the intervention. And based on the Chi-Square analysis test, a p value <0.05 was obtained for the influence of respondent actions with the presence of larvae. Conclusion: There is an influence between respondent actions in efforts to eradicate mosquito nests with the presence of dengue mosquito larvae in their home environment in Rappocini District, Makassar City.